Animal studies reveal that the ghrelin pathway regulates alcohol-mediated responses - Jerlhag, Elisabet (Frontiers in Psychiatry, 2023)
Alcohol use disorder (AUD) is often described as repeated phases of binge drinking, compulsive alcohol-taking, craving for alcohol during withdrawal and drinking with an aim to a reduce the negative consequences. Although multifaceted, alcohol-induced reward is one aspect influencing the former three of these. The neurobiological mechanisms regulating AUD processes are complex and one of these systems is the gut-brain peptide ghrelin. The vast physiological properties of ghrelin are mediated via growth hormone secretagogue receptor (GHSR, ghrelin receptor). Ghrelin is well known for its ability to control feeding, hunger and metabolism. Moreover, ghrelin signaling appears central for alcohol-mediated responses; findings reviewed herein. In male rodents GHSR antagonism reduces alcohol consumption, prevents relapse drinking, and attenuates the motivation to consume alcohol. On the other hand, ghrelin increases the consumption of alcohol. This ghrelin-alcohol interaction is also verified to some extent in humans with high alcohol consumption. In addition, either pharmacological or genetic suppression of GHSR decreases several alcohol-related effects (behavioral or neurochemical). Indeed, this suppression blocks the alcohol-induced hyperlocomotion and dopamine release in nucleus accumbens as well as ablates the alcohol reward in the conditioned place preference model. Although not fully elucidated, this interaction appears to involve areas central for reward, such as the ventral tegmental area (VTA) and brain nodes targeted by VTA projections. As reviewed briefly, the ghrelin pathway does not only modulate alcohol-mediated effects, it regulates reward-related behaviors induced by addictive drugs. Although personality traits like impulsivity and risk-taking behaviors are common in patients with AUD, the role of the ghrelin pathway thereof is unknown and remains to be studied. In summary, the ghrelin pathway regulates addiction processes like AUD and therefore the possibility that GHSR antagonism reduces alcohol or drug-taking should be explored in randomized clinical trials.